Combating Corruption as a Means of Ensuring the Legality of Public Authorities - S. V. Vedyashkin (Courier of Kutafin Moscow State Law University (MSAL)), 2026)
The article discusses the improvement of the mechanism for countering corruption in the activities of public authorities as a means of ensuring the rule of law, and raises the question of its content. The article assesses the role of means of ensuring the rule of law and highlights the elements in the mechanism for countering corrupt acts of behavior. The study of legal acts regulating anti-corruption measures and doctrinal provisions has provided significant practical suggestions, including the allocation of an independent chapter in the Code of Administrative Offenses of the Russian Federation, which correlates with criminal law norms that contain administrative legal preclusion.